A Numerical Method to Enhance the Performance of a Cam‐Type Electric Motor‐Driven Left Ventricular Assist Device. Issue 10 (2nd May 2013) - Huang, Huan; Yang, Ming; Lu, Cunyue; Xu, Liang; Zhuang, Xiaoqi; Meng, Fan
Abstract Pulsatile left ventricular assist devices (LVADs) driven by electric motors have been widely accepted as a treatment of heart failure. Performance enhancement with computer assistance for this kind of LVAD has seldom been reported. In this article, a numerical method is proposed to assist the design of a cam‐type pump. The method requires an integrated model of an LVAD system, consisting of a motor, a transmission mechanism, and a cardiovascular circulation. Performance indices, that is, outlet pressure, outlet flow, and pump efficiency, were used to select the best cam profile from six candidates. A prototype pump connected to a mock circulatory loop (MCL) was used to calibrate the friction coefficient of the cam groove and preliminarily evaluate modeling accuracy. In vitro experiments show that the mean outlet pressure and flow can be predicted with high accuracy by the model, and gross geometries of the measurements can also be reproduced. Simulation results demonstrate that as the total peripheral resistance (TPR) is fixed at 1.1 mm Hg.s/mL, the two‐cycle 2/3‐rise profile is the best. Compared with other profiles, the maximum increases of pressure and flow indices are 75 and 76%, respectively, and the maximum efficiency increase is over 51%. For different TPRs (0.5∼1.5 mm Hg.s/mL) and operation intervals (0.1∼0.4 s) in counterpulsation, the conclusion is also acceptable.